O-003 The SelecTIMO study - clinical outcomes of uninterrupted embryo culture with or without time-lapse based embryo selection versus interrupted standard culture: a randomized controlled trial. (30th June 2022) - Kieslinger, D C; Vergouw, C G; Ramos, L; Arends, B; Curfs, M H J M; Slappendel, E; Kostelijk, E H; Pieters, M H E C; Consten, D; Verhoeven, M O; Besselink, D E; Broekmans, F; et al.
Abstract: Study question: Does uninterrupted embryo culture with or without the application of a time-lapse monitoring (TLM) selection algorithm lead to higher (cumulative) ongoing pregnancy rates? Summary answer: Uninterrupted embryo culture with or without a TLM selection algorithm and interrupted culture with morphological embryo selection all resulted in comparable (cumulative) ongoing pregnancy rates. What is known already: The application of TLM for embryo development has been claimed to improve success rates of IVF and ICSI treatments. Systematic reviews, however, show that evidence supporting the routine clinical use of TLM in IVF laboratories is limited and well-designed RCTs are needed to assess its clinical value. The uninterrupted and stable culture conditions in a TLM incubator may cause an increase of the clinical success rate independent from a possible improvement mediated by TLM based embryo selection procedures. Therefore, three study groups were needed to distinguish these two mechanisms. Study design, size, duration: In this multicenter, double-blind, superiority RCT, women were prospectively randomized in three groups between 2017-2020: 1) TLE (Time-Lapse Eeva): embryo selection based on the Eeva® Test (a day three TLM algorithm, used adjunctively with morphology) and uninterrupted culture. 2) TLR (Time-Lapse Routine): routine morphological embryo selection and uninterrupted culture. 3) CON (Control): routine morphological embryo selection and interrupted culture. Embryos were cultured in Geri+ incubators. Randomization was stratified for laboratory-site and ovum pickup number. Participants/materials, setting, methods: Women scheduled for day three single embryo transfer (SET) during their first, second or third ovum pickup were included. Primary endpoints were: 1) cumulative ongoing pregnancy rate (cOPR) including fresh SET and associated cryo transfers within 12 months of all women; 2) ongoing pregnancy rate (OPR) after fresh SET in a good-prognosis population: women <41.0 years, ≥5 oocytes, ≥4 fertilized oocytes. Odds ratios (OR) with 95% CI were adjusted for laboratory-site and ovum pickup number. Main results and the role of chance: A total of 1731 women were randomly assigned to TLE (577), TLR (579) or CON (575). The 12 month cOPR did not differ significantly between the groups (p = 0.85) with a cOPR of 50.8% (293/577) in TLE, 50.9% (295/579) in TLR and 49.4% (284/575) in CON (TLE vs TLR: OR 0.99, 95% CI 0.79 – 1.25; TLE vs CON: OR 1.06, 95% CI 0.84 – 1.33; CON vs TLR: OR 0.94, 95% CI 0.75 – 1.19). In the good-prognosis population, the OPR after fresh SET was 38.2% (125/327) in TLE, 36.5% (118/323) in TLR and 37.8% (123/325) in CON (p = 0.90). Consistent results were found for pregnancy and live birth rates after fresh embryo transfer and cumulatively within one year. A planned subgroup analysis of three female age groups revealed interaction between age group and treatment on cOPR (p = 0.02). In women of 39 years and older (n = 245), the cOPR was higher in TLE compared to TLR (40.0% vs 23.7%: OR 2.10, 95% CI 1.05-4.21) with no difference between TLE vs CON (40.0% vs 31.5%: OR 1.44, 95% CI 0.76-2.71). Limitations, reasons for caution: This study investigated embryo culture in the Geri+ incubator and the Eeva® Test algorithm, which predicts blastocyst formation on day three and was used in combination with morphology for embryo selection, while more TLM systems and algorithms are currently available. Wider implications of the findings: Neither embryo selection based on a TLM selection algorithm in combination with morphology (TLE) nor the uninterrupted culture conditions in the Geri+ incubator (TLR) improved (cumulative) ongoing pregnancy and live birth rates after IVF or ICSI. Widespread application for fertility treatments with the promise of improved outcomes should be questioned. Trial registration number: NL5314